COVID-19, Climate, and White Supremacy: Multiple Crises or One? - Rohland, Eleonora (Journal for the History of Environment and Society, 2020)
Abstract This essay asks whether there is a connection between the three crises that are currently reverberating globally, the climate crisis, the COVID-19 crisis and the ‘crisis of white supremacy’. The latter resurfaced violently at first in the US with the murder of the African-American citizen George Floyd on May 25 at the hands of US police. This contribution argues that the parallel occurrence of these three crisis-like processes, which unfold on divergent time scales, is not a coincidence and that they are, indeed, connected. Using approaches from historical disaster research and the history of environmental entanglements, the essay highlights the vulnerability of specific population groups that has grown over the historical longue durée, both in the context of the climate crisis and in the context of the pandemic. In a second step, the contribution embeds the climate and corona crises as partial crises in the larger context of the Anthropocene. By going back to the colonial prehistory of this new ‘Age of humans’, the essay shows how extreme resource exploitation and the accompanying destruction of nature - as a precondition for today’s climate change and zoonosis-induced pandemics - are intertwined with white superiority thinking and systemic racism.